Effects of once-weekly semaglutide on coronary outcomes in patients with type 2 diabetes mellitus with or at high risk for cardiovascular disease: insights from the SUSTAIN-6 trial. (11th May 2022) - Kolkailah, A; Aharonovich, A; Lingvay, I; Dobrecky-Mery, I; Rasmussen, S; Tetens Hoff, S; Mcguire, DK
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Nordisk A/S Background/introduction: In the randomised, double-blind, placebo-controlled SUSTAIN-6 cardiovascular (CV) outcomes trial, once-weekly (OW) semaglutide (a glucagon-like peptide-1 receptor agonist), compared with placebo, reduced the risk of major adverse CV events (CV death, non-fatal myocardial infarction [MI], or non-fatal stroke) and the risk for revascularisation (pre-specified secondary outcome) in patients with type 2 diabetes mellitus (T2DM) with or at high risk for CV disease (CVD). However, the effects of OW semaglutide on composite coronary-specific outcomes have not been explored. Purpose: The aim of these post-hoc, exploratory analyses was to assess the effects of OW semaglutide, compared with placebo, on composite coronary outcomes in the SUSTAIN-6 trial population. Methods: In these post-hoc analyses of the SUSTAIN-6 trial, the following coronary outcomes were assessed with OW semaglutide (0.5 and 1.0 mg doses pooled) vs placebo, both in addition to standard of care: the main coronary outcome (composite of MI [both fatal and non-fatal] or coronary revascularisation [defined as coronary artery bypass graft surgery or percutaneous coronary intervention]); and the expanded coronary outcome (composite of MI, coronary revascularisation, or unstable angina). Coronary outcomes were assessed overall, as well as in subgroups with or without a prior coronary event (MI or coronary revascularisation) at baseline. Cox proportional hazards regression models were used to analyse time to first event for the outcomes. Results: Overall, 3, 297 patients were included in these analyses. Key cohort characteristics included a mean age of 64.6 ± 7.4 years with an average T2DM duration of 13.9 ± 8.1 years; 39.3% were female and 48.3% had prior MI or coronary revascularisation (32.5% and 40.3% for each prior event, respectively). The median follow-up duration was 2.1 years. The proportion of patients experiencing a first event was lower with OW semaglutide vs placebo for the main coronary outcome (6.1% vs 8.1%; hazard ratio [HR] 0.74 [95% confidence interval (CI) 0.57–0.97]) and the expanded coronary outcome (6.3% vs 8.6%; HR 0.73 [95% CI 0.56–0.94]) (Figure 1). The time to the first main coronary outcome event is shown in Figure 2. Prior coronary event status at baseline did not modify the treatment effects of semaglutide (all p-interaction >0.05) (Figure 1). Conclusions: In these post-hoc analyses of the SUSTAIN-6 trial, OW semaglutide reduced the risk of composite coronary outcomes vs placebo in patients with T2DM with or at high risk for CVD, irrespective of prior MI or revascularisation status. These findings support the beneficial effects of OW semaglutide in this high risk population.